A code biology analysis of the regulatory regions in cell lines - Paredes, Omar; May-Canche, Isaías; Fimmel, Elena (Revista Mexicana de Ingenieria Biomedica, 2018)
Coding sequences are widely studied for their relevance in protein synthesis. However, higher organism genomes, such as human ones, has a small amount of them, and a larger proportion of non-coding sequences. ENCODE and Epigenomic Roadmap projects discovered that regulatory functions are carried out in the non-coding regions of the human genome. These regulatory functions are part of the regulatory machinery that yields different gene expression profiles, thus, different cell lines. Whereas different environmental elements, i. e. histone modifications, DNA methylation, and other epigenomic phenomena, determine the regulatory function of genome part, the sequences’ composition where these functions take place could also influence regulatory machinery. In this work, we explore the non-coding regulatory sequences and lexica build with subsequences between 3 and 16 nucleotides to evaluate the difference between the sequence composition of the regulatory regions in the cell lines. Our results show that the lexica corresponding to the regulatory regions are different based on their complexity/degeneracy, moreover, the lexica of regulatory regions in different cell lines are also different. These features suggest that non-coding sequences are an active element of the regulatory machinery and the histone code that are involved in cell differentiation.